Mutation Patterns in Portuguese Families with Hereditary Breast and Ovarian Cancer Syndrome - Vicente, Rodrigo (2022)
Funding Information: The authors R.V., M.V., A.D.M. and C.S. declare no conflict of interest. D.A.C. has received honoraria from the Portuguese Navy, CUF Oncologia, and NTT DATA, and has served as a speaker, advisory board member, or has received research or education funding from AstraZeneca, CUF Oncologia, Daiichi Sankyo, Gilead, Hoffmann-La Roche, Merck KGaA, Merck Sharp & Dohme, Nestlé, Novartis, Pfizer, Nanobiotix, Puma Biotechnology Inc., Sanofi, Seagen Inc., and Uriage. MFS is a consultant/speaker for Astellas, Daiichi-Sankyo, Bristol Myers Squibb, Gilead, Lilly, Merck, Merck Sharp & Dohme, Novartis, Pfizer, Pierre-Fabre Ipsen, Roche and Server. Publisher Copyright: © 2022 by the authors.